Molecular Testing of Lymphoproliferative Disorders: Current Status and Perspectives - Yoon Kyung Jeon; Sun Och Yoon; Jin Ho Paik; Young A Kim; Bong Kyung Shin; Hyun-Jung Kim; Hee Jeong Cha; Ji Eun Kim; Jooryung Huh; Young-Hyeh Ko (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Molecular pathologic testing plays an important role for the diagnosis, prognostication and decision of treatment strategy in lymphoproliferative disease. Here, we briefly review the molecular tests currently used for lymphoproliferative disease and those which will be implicated in clinical practice in the near future. Specifically, this guideline addresses the clonality test for B- and T-cell proliferative lesions, molecular cytogenetic tests for malignant lymphoma, determination of cell-of-origin in diffuse large B-cell lymphoma, and molecular genetic alterations incorporated in the 2016 revision of the World Health Organization classification of lymphoid neoplasms. Finally, a new perspective on the next-generation sequencing for diagnostic, prognostic, and therapeutic purpose in malignant lymphoma will be summarized.